PROBLEMATIKA HUKUM ARBITRASE ONLINE MENURUT UU NO. 30 TAHUN 1999 TENTANG ARBITRASE DAN ALTERNATIF PENYELESAIAN SENGKETA - Ilham Bagaskara Aji; , Pujiyono (Jurnal Privat Law, 2020)
AbstractThis article describes and examines the problem, first, the legal standing of the Arbitration Online  according to Law No. 30 of 1999 concerning Arbitration and Alternative Dispute Resolution. Secondly, there are legal problems if online arbitration is carried out in Indonesia. This research is prescriptive normative legal research. Types of data and sources of research material include primary and secondary legal materials. The data collection technique used is the study of literature and through Cyber media, furthermore the technical analysis used is the deductive method. The results show that online arbitration can actually be carried out in Indonesia. Through Law No. 11 of 2008 concerning Electronic Information and Transactions that were changed using Law No. 19 of 2016 concerning Amendments to Law No. 11 of 2008 and Government Regulation No. 71 of 2019 concerning the Implementation of Electronic Transactions and Systems the government has provided the means and foundation for carrying out online arbitration. Online arbitration has advantages in the speed and efficiency of dispute resolution times. However, online Aribtrase also has some disadvantages such as how to registering decisions in court, the presence of witnesses in court, piracy and hacking, and unequal electronic means.Keywords: Alternative Dispute Resolution; Online Arbitration; Electronic Document; Law No. 30 of 1999AbstrakArtikel ini ini mendeskripsikan dan mengkaji permasalahan, pertama, kedudukan hukum Arbitrase  Online menurut UU No. 30 Tahun 1999 tentang Arbitrase dan Alternatif Penyelesaian Sengketa. Kedua, problem hukum apabila arbitrase online dilaksanakan di Indonesia. Penelitian ini adalah penelitian hukum normatif bersifat preskriptif. Jenis data dan sumber bahan penelitian meliputi bahan hukum primer dan sekunder. Teknik pengumpulan data yang digunakan adalah studi kepustakaan dan melalui Cyber media, selanjutnya teknis analisis yang digunakan adalah metode deduktif. Hasil penelitian menunjukkan bahwa arbitrase online sebenarnya sudah dapat dilaksanakan di Indonesia. Melalui Undang- Undang No. 11 Tahun 2008 tentang Informasi dan Transaksi Elekronik yang diubah menggunakan Undang- Undang No. 19 Tahun 2016 tentang Perubahan Atas Undang- Undang No. 11 Tahun 2008 serta Peraturan Pemerintah No. 71 Tahun 2019 tentang Pelaksanaan Sistem dan Transaksi Elektronik pemerintah telah memberikan sarana dan landasan untuk melaksanakan arbitrase online. Arbitrase online memiliki kelebihan dalam kecepatan dan efisiensi waktu penyelesaian sengketa. Akan tetapi arbitrase online juga memiliki beberapa kekurangan seperti bagaimana pendaftaran putusan di pengadilan, kehadiran para saksi dalam persidangan, pembajakan dan peretasan, dan sarana elektronik yang kurang merata.Kata Kunci: Alternatif Penyelesaian Sengketa; Arbitrase Online; Dokumen Digital; UU No. 30 Tahun 1999